2019
DOI: 10.1002/ijc.32071
|View full text |Cite|
|
Sign up to set email alerts
|

ETS variant 5 promotes colorectal cancer angiogenesis by targeting platelet‐derived growth factor BB

Abstract: ETS transcription factors play important roles in tumor cell invasion, differentiation and angiogenesis. In this study, we initially demonstrated that ETS translocation variant 5 (ETV5) is abnormally upregulated in colorectal cancer (CRC), is positively correlated with CRC tumor size, lymphatic metastasis and tumor node metastasis (TNM) stage and indicates shorter survival and disease‐free survival in CRC patients. In vitro and in vivo experiments revealed that the downregulation of ETV5 could significantly su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 39 publications
4
41
0
1
Order By: Relevance
“…Some previous studies also revealed that the ETS family triggered angiogenesis in multiple tumors [13,17,18]. Similarly, our previous study showed that ETV5 facilitated CRC angiogenesis via PDGF-BB/Src/STAT3/VEGFA signaling pathway [19]. Besides, more and more studies indicated that chemokine signaling played critical roles in tumor angiogenesis, such as CCL2/CCR2 signaling and CXCL11/CXCR7 signaling [20,21].…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…Some previous studies also revealed that the ETS family triggered angiogenesis in multiple tumors [13,17,18]. Similarly, our previous study showed that ETV5 facilitated CRC angiogenesis via PDGF-BB/Src/STAT3/VEGFA signaling pathway [19]. Besides, more and more studies indicated that chemokine signaling played critical roles in tumor angiogenesis, such as CCL2/CCR2 signaling and CXCL11/CXCR7 signaling [20,21].…”
Section: Introductionmentioning
confidence: 57%
“…Lentiviral particles were transduced into CRC cells according to the manufacturer's instructions, followed by stable selection. Lentivirus transfection was performed as described previously [19]. Antibiotic puromycin was used to select stably transfected cells.…”
Section: Generation Of Gene Overexpressing and Knocked Down Cellsmentioning
confidence: 99%
See 3 more Smart Citations